(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present study is aimed to investigate the safety and reliability of anti diabetic drug Metformin and possible drug interaction with Pravastatin when they were administered as combination treatment. The study was conducted on healthy Wistar and streptozotocin induced diabetic rats. A simple and sensitive high performance liquid chromatographic method was developed for the simultaneous estimation of Metformin and Pravastatin in rat plasma and also to estimate possible pharmacokinetic parameters of these drugs after oral administration. There was no significant difference in the tmax of Metformin alone and combination with Pravastatin on day 1 and day 8 respectively. These were no significant increase in both AUC (0 – 24 h) and AUC (0 - ) of Metformin alone and combination of Pravastatin on day 1 and day 8 respectively. Similarly there was no significant enhancement in the Cmax between Metformin alone and combination with Pravastatin on day 1 and day 8 respectively. There is however no significant difference in Cmax, t½, values. Similarly there was no significant difference in the tmax of Pravastatin alone and combination with Metformin on day 1 and day 8 respectively and no significant enhancement in Cmax, tmax, t1/2, values between Pravastatin alone and combination with Metformin on day 1 and day 8 respectively. In the present study, based on the results it can be concluded that the concurrent administration of these two drugs have potential benefit in the treatment of Diabetes and hyperlipidemia. In addition, due to their insignificant pharmacokinetic interaction the combinational therapy can be safe and highly advantageous in hyperlipidemia patients with diabetes.